Analisis Pelaksanaan Pendidikan Multikultural oleh Guru Kelas SD - Lisnawati Aprilia; M. Defriansyah Angga Putra Nina Kardina; Seprianto Seprianto (Journal of Elementary School (JOES), 2023)
SD Negeri 06 Muara Rupit is one of the schools located in the district capital in the Muara Rupit sub-district, Rupit sub-district, North Musi Rawas Regency. This study aims to describe the Analysis of the Implementation of Multicultural Education by Classroom Teachers in schools with case studies at SD Negeri 6 Muara Rupit in 2022. The facts revealed are described in words and actions, so this research uses a qualitative approach. Data analysis applies an interactive model through interviews, data collection, data reduction, data presentation and drawing conclusions. The results of the study show that there is multicultural equality, differences in religion and ethnicity in the multicultural interactions of class VI students at SD Negeri 06 Muara Rupit based on religion and ethnicity, religious status consisting of Islam and Christianity. The existing tribes are the Rawas tribe and the Anak Dalam tribe. Efforts made by the class teacher to strengthen self-confidence and reinforce these students and apply mutual respect and a sense of kinship with friends around them. Keywords: multicultural, class teacher